THE INFLUENCE OF TERROR ON THE PERSONALITY OF THE MAIN CHARACTERS IN FOUR SHORT STORIES BY STEPHEN KING - Sandi, Sandi; Widisanti, Ni Made; Setyowati, Agnes (Universitas Pakuan, 2022)
This study discusses the influence of terror on the main character's personality in four short stories by Stephen King. In Stephen Kings short stories Mr. Harrigan's Phone, The Life of Chuck, If it Bleeds and The Rat, terror occurs because of the unusual change in certain objects. People are mostly not accustomed to being aware of terror. Theoretically, terror has certainly been used to gain power and political achievement for centuries. The descriptive qualitative analysis method is applied in this research. The finding posits that people affected by terror usually have psychological reactions such as anxiety/fear and curiosity. Therefore, someone tries to fight it as a form of self-defense. If an individual is constantly exposed to terror, it can potentially change ones personality.Keywords:influence; terror; personality; main character; reaction; anxiety; curiosity; self-defense.